2005
DOI: 10.1007/s00439-005-0080-2
|View full text |Cite
|
Sign up to set email alerts
|

Admixture-matched case-control study: a practical approach for genetic association studies in admixed populations

Abstract: Case-control genetic association studies in admixed populations are known to be susceptible to genetic confounding due to population stratification. The transmission/disequilibrium test (TDT) approach can avoid this problem. However, the TDT is expensive and impractical for late-onset diseases. Case-control study designs, in which cases and controls are matched by admixture, can be an appealing and suitable alternative for genetic association studies in admixed populations. In this study, we applied this match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 51 publications
4
35
0
1
Order By: Relevance
“…It is argued that admixture-matched case-control strategies can efficiently control population stratification, 82 particularly collecting as much information about ethnicity as possible, in order to provide an accurate ethnic stratification and reduce false-positive results. However, this view is not consensual 83 and, particularly in Brazil, it has been demonstrated that physical appearance or self-reported background are not efficient predictors of genomic ancestrality.…”
Section: Ethnic Characteristics Of the Brazilian Populationmentioning
confidence: 99%
“…It is argued that admixture-matched case-control strategies can efficiently control population stratification, 82 particularly collecting as much information about ethnicity as possible, in order to provide an accurate ethnic stratification and reduce false-positive results. However, this view is not consensual 83 and, particularly in Brazil, it has been demonstrated that physical appearance or self-reported background are not efficient predictors of genomic ancestrality.…”
Section: Ethnic Characteristics Of the Brazilian Populationmentioning
confidence: 99%
“…Recruitment and patient characteristics are described elsewhere and in detail in the online supplement (19). Briefly, as part of the Study of African Americans, Asthma, Genes, and Environments (SAGE), investigators recruited cases and control subjects from community clinics within San Francisco and Oakland, California.…”
Section: Study Participantsmentioning
confidence: 99%
“…One of the problems of conducting association studies in miscegenated populations by using only self-reported ancestry or skin color as equivalents of ethnicity is the possibility of a spurious association with false-positive or false-negative results [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In most of the studies, single nucleotide polymorphisms (SNPs) were used [30][31][32][33], but insertion/deletion markers (INDELs) with small DNA fragments [29,34] and Short Tandem Repeats (STRs) [35] have also been employed.…”
Section: Introductionmentioning
confidence: 99%